A case of medical tourism? - Théo Maurette; Sami Ben Fguira (Via@)
The reception of foreign patients in Sfax (Tunisia) in exclusively private healthcare facilities raises questions about the place of medical tourism in patient-caregiver relationships. While medical tourism is a decried notion, it is above all part of an economic and globalized vision of health exchanges. Mobilities for medical reasons are local and constrained rather than chosen, within a global market. However, the case of Sfax shows that medical tourism is also a specific governmentality, constructed by supply and demand, outside the standards of mass tourism. First of all, informal practices surrounding care produce a form of “desire” for Sfax, also embedded in the neoliberal context surrounding the development of this activity. This gives the biopolitical reading a transcalar and analytical force of the phenomenon of medical tourism, within transnational care spaces.